2011
DOI: 10.1128/cvi.00460-10
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 4 Gene ( TLR4 ), but Not TLR2 , Polymorphisms Modify the Risk of Tonsillar Disease Due to Streptococcus pyogenes and Haemophilus influenzae

Abstract: Tonsillar disease (recurrent tonsillitis and/or tonsillar hypertrophy) is one of the most common human disorders, with Streptococcus pyogenes (group A beta-hemolytic streptococcus [GAS]) and Haemophilus influenzae representing the most common pathogens. Until now, no study has investigated why some individuals are more susceptible to tonsillar infections caused by specific bacteria than others. The aim of this study was to uncover possible associations between common Toll-like receptor gene (TLR) polymorphisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 34 publications
1
36
0
5
Order By: Relevance
“…The frequencies of the TLR4 SNPs in Omani HIV-infected and control individuals enrolled in this study were similar to those found in Spanish HIV-infected and control individuals (Soriano-Sarabia et al, 2008). Moreover, the frequencies in the healthy population were similar to those in patients with tonsillar disease and infected with Streptococcus pyogenes (Liadaki et al, 2011). The significant difference in the frequency of TLR4 1063GG genotype between the HIV-infected patients and the control group might be due to differences in the ethnic background of the enrolled individuals in both groups although they are all Omanis.…”
Section: Discussionsupporting
confidence: 58%
“…The frequencies of the TLR4 SNPs in Omani HIV-infected and control individuals enrolled in this study were similar to those found in Spanish HIV-infected and control individuals (Soriano-Sarabia et al, 2008). Moreover, the frequencies in the healthy population were similar to those in patients with tonsillar disease and infected with Streptococcus pyogenes (Liadaki et al, 2011). The significant difference in the frequency of TLR4 1063GG genotype between the HIV-infected patients and the control group might be due to differences in the ethnic background of the enrolled individuals in both groups although they are all Omanis.…”
Section: Discussionsupporting
confidence: 58%
“…Moreover, a protective effect TLR4 SNPs against infections was also reported by other non-ICU studies (Hawn et al 2009;Liadaki et al 2011;Yuan et al 2008). The reason why the impact of TLR4 polymorphisms in susceptibility to sepsis differs in medical and surgical patients is not obvious.…”
Section: Nomentioning
confidence: 51%
“…As mentioned above, both TLR4 SNPs are usually detected in a co-segregated state (Arbour et al 2000;Ferwerda et al 2008;Liadaki et al 2011;Speletas et al 2009); the impact of this linkage has not been fully explored. Carriers of both TLR4 SNPs may appear in four haplotypes, namely wt/wt, D299G/wt, T399I/wt and D299G/T399I.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…TLR4 missense mutations might act in concert with other genetic changes to influence the complex immunologic response; they may also be modifying factors for AH and other phenotypes, and particularly for allergies and asthma (4). Recently it was shown that TLR4 mutations are linked to an increased risk of recurrent tonsillitis and/or tonsillar hypertrophy (31). The adenoids are similar to tonsils, and they are important components of the lymphoid tissue situated in the upper airways, known as Waldeyer's ring (1).…”
Section: Discussionmentioning
confidence: 99%